Study of the Responsibility and the Satisfaction of Students using the “Flipped Classroom” in the Subject of English for Global Communication - Nuiplot, Nalin-on; Songyoo, Rojjanant; Phieanchang, Thanahnahphatt (วารสารวิชาการนอร์ทเทิร์น, 2024)
The research entitled “Study of the Responsibility and the Satisfaction of Students using the “Flipped Classroom” in the Subject of English for Global Communication” aimed to 1) study the responsibility in English Subject learning between Flipped Classroom and non-Flipped Classroom and 2) study the satisfaction of students to the Flipped Classroom as a learning management in English Subject learning. The samples group was the 96 students enrolled in English for Global Communication Subject, General Education program, Valaya Alongkorn Rajabhat University under the Royal Patronage, Pathum Thani, Thailand, in the second semester of academic year 2022 by purposively selected. The tools used in this research were: the “Project Evaluation” form, and the online questionnaire which was in the title of “Satisfaction of Students to the Flipped Classroom”. The statistics used in this research was Percentage, Mean, Standard Deviation and t-test for dependent samples. It was found that 1) the responsibility score in English subject learning of students in Flipped Classroom was higher than the non-Flipped Classroom with reliability value at 0.05 in both separate and whole aspects, and 2) the satisfaction of students to the Flipped Classroom as a learning management of English subject was at the highest level in both separate and whole aspects.